2013
DOI: 10.1089/aid.2012.0314
|View full text |Cite
|
Sign up to set email alerts
|

High Percentage of Recent HIV Infection Among HIV-Positive Individuals Newly Diagnosed at Voluntary Counseling and Testing Sites in Poland

Abstract: To gain insight into HIV transmission we estimated the proportion of those recently infected. We examined data from HIV-positive patients and a random 10% sample of HIV-negative patients tested at Voluntary Counseling and Testing sites in Poland in 2006. Archived samples from positive patients were tested by three assays to differentiate recent from long-standing infection. Using logistic regression, we examined the association of recent infection (at least one assay) with age, sex, HIV exposure category, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
1
13
0
1
Order By: Relevance
“…Although this increase alone would not fully explain the notification trend, it indicates that an upsurge of new HIV infections may also play a role. To further support the hypothesis of increasing HIV incidence among MSM, other studies found a high proportion (>30%) of recent infections confirmed by recent infection testing algorithm (RITA) testing among new diagnoses among MSM [18,19]. On the other hand, the proportions of respondents in behavioural surveys who reported having ever been tested were comparable in 2004 and 2010, 57% and 62% respectively, although it must be borne in mind that the study designs were different [15,16].…”
Section: Discussionmentioning
confidence: 97%
“…Although this increase alone would not fully explain the notification trend, it indicates that an upsurge of new HIV infections may also play a role. To further support the hypothesis of increasing HIV incidence among MSM, other studies found a high proportion (>30%) of recent infections confirmed by recent infection testing algorithm (RITA) testing among new diagnoses among MSM [18,19]. On the other hand, the proportions of respondents in behavioural surveys who reported having ever been tested were comparable in 2004 and 2010, 57% and 62% respectively, although it must be borne in mind that the study designs were different [15,16].…”
Section: Discussionmentioning
confidence: 97%
“…9 Negative attitudes toward people reporting risky behavior may be especially harmful and are often seen in medical settings and among medical workers not used to such patients. [10][11][12] Although different venues have been created to increase HIV testing (VCT centers, medical clinics, checkpoints, club testing, home sampling, home testing), no diagnosed individual should be left without referral to HIV clinics, where proper medical care and treatment can be offered. Proper linkage to care helps to achieve both individual and epidemiological goals of reducing the HIV burden and increasing fund efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the tests for the HIV infection are performed in Poland in two ways. First of all, by the carrying out of the programme of the anonymous testing in the Voluntary Counselling and Testing Centres (VCT) (Polish abbreviation: PKD) based on the analysis of the risk factors [22]. This system detects around 1.3% of new HIV infections which indicates its high effectiveness [23].…”
Section: Discussionmentioning
confidence: 99%